ZCT 304E/3 - Electricity and Magnetism II - February - March 2003 - PPSF, Pusat Pengajian Sains Fizik (2003)
UNIVERSITI SAINS MALAYSIA Second Semester Examination 2002/2003 Academic Session February - March 2003 ZCT 304E/3 - Electricity and Magnetism II Time : 3 hours